Aging and pension reform: extending the retirement age and human capital formation - Edgar Vogel; Alexander Ludwig; Axel Börsch-Supan (European Central Bank (ECB), 2012)
Projected demographic changes in industrialized countries will reduce the share of the working-age population. Analyses based on standard OLG models predict that these changes will increase the capital- labor ratio. Hence, rates of return to capital decrease and wages increase with adverse welfare consequences for current middle aged asset rich agents. This paper addresses three important adjustments channels to dampen these detrimental effects of demographic change: investing abroad, endogenous human capital formation and increasing the retirement age. Our quantitative finding is that openness has a relatively mild effect. In contrast, endogenous human capital formation in combination with an increase in the retirement age has strong effects. Under these adjustments maximum welfare losses of demographic change for households alive in 2010 are reduced by about 3 percentage points.
Keywords: C68; E17; E25; J11; J24; 330; Human capital; open economy; pension reform; Population aging; retirement age; Welfare